Moderating Role of Spirituality between Occupational Stress and Work-Family Conflict among COVID-19 Rescue Responders - Muhammad Yasir Raza, Syed Messum Ali Kazmi, Iqra Batool, Fayyaz Ahmed Anjum, Maham Rasheed, (Pakistan Journal of Medical & Health Sciences, 2022)
COVID-19 has become a global pandemic which has affected millions of people worldwide. It has become a global issue for the people of the world. The current study aimed to find whether there is any relationship between spirituality, Occupational stress and work family conflict among COVID-19 rescue responders or not. A sample of 180 COVID-19 rescue responders was selected through purposive sampling by selecting 5 rescue responders from each district of Punjab Province. Co relational research design used for this study and Data was collected by administering Health Safety Executive Standard Indicator Tool for occupational stress, Work Family Conflict Self Efficacy scale for work family conflict and Multidimensional Measure for Islamic Spirituality to rescue responders. Data was analyzed though SPSS by using statistical processes of regression, correlation and moderation along with calculating Percentage and frequencies of responses. Results of the study showed that spirituality moderates the relationship between occupational stress and work family conflict among COVID-19 rescue responders. It also showed that there was no significant effect of demographic variables on occupational stress, work family conflict and spirituality. This study is the first study on COVID-19 rescue responders. More research work may be done by other researchers to fully explore different aspects of spirituality, occupational stress and work family conflict among Rescue responders and emergency responders. Keywords: Spirituality, Occupational stress, Work Family Conflict, COVID-19, Rescue Responders.